Clinically Significant Gastrointestinal Bleeding Using Proton Pump Inhibitors or Histamine Type-2 Receptor Antagonists in Patients Intubated for Over 48 Hours: : A Systematic Review and Meta-Analysis - Khokher, Waleed (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.